IDENTIFY THE EFFECT OF ALTITUDE ON THE MORPHOLOGY OF SUGAR PALM PLANTS - Halimatus Syahdia Hasibuan; Muhammad Parikesit Wisnubroto; Dewi Rezki (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
Indonesia needs to diversify cane sugar into brown sugar to reduce imports of cane sugar. Excessive consumption of cane sugar is one of the causes of the increase in diabetes mellitus sufferers. The sugar palm plant as a producer of brown sugar has the potential to be developed as a substitute for cane sugar. Identification of sugar palm plants is carried out to determine genetic diversity. High genetic diversity also has high adaptability. This research aims to determine differences in the morphological characteristics of sugar palm plants based on different altitudes and identify the level of uniformity of morphological characteristics in sugar palm plants. The results of these observations are used as initial data to determine the parent tree that will be used as propagation material. The research was conducted in North Lintau Buo District, Tanah Datar Regency, West Sumatra from September to October 2024. Sampling locations were taken based on different altitudes with three plant samples per altitude until nine plant accessions were obtained. The research results showed that the quantitative and qualitative characters of sugar palm plants had relatively narrow phenotypic variability values. The kinship analysis of sugar palm plants has a level of similarity with a coefficient value of 10.13 – 80.39%. The closest relationship distance is shown in accession 8 and accession 9, with a similarity level of 80.39%. Meanwhile, accession 4 has a distant relationship with accessions 1, 3, 2, 7, 8, 9, 6, and 5 with a similarity level of only 10.13%. PCA analysis shows that accession 4 is different from other accessions based on the characteristics of bark color, frond shape, petiole shape, and build leaflets.